Prognostic Factors in Patients with Rocky Mountain Spotted Fever - Hiram J. Jaramillo-Ramírez; Jeremy J. Hernández-Ríos; Fátima M. Martínez-González; Luz A. Gutiérrez-Bañales; Eliot R. García-Valenzuela; J. Andrés Beltrán-López; Jorge L. Peterson; Flor M. Yocupicio; Rodolfo Ruíz-Luján (University Library System, University of Pittsburgh, 2020)
Background: Rocky Mountain Spotted Fever (RMSF) is a disease with a high mortality rate, caused by Rickettsia rickettsii, a bacteria transmitted to humans by infected ticks. In 2008 there was a Rocky Mountain Spotted Fever (RMSF) outbreak in the city of Mexicali, México, resulting in an increased mortality rate amongst the area population. Methods: Case-series study of patients admitted to the General Hospital of Mexicali between 2014 and 2019 with a confirmed diagnosis of RMSF. Mortality was compared dividing the population on those ?20 and younger than ?21 years of age. Results: A total of 129 patients' records during a 5-year period whose diagnosis was RMSF confirmed with PCR were included. Mortality was compared among patients admitted who were younger than ?20 years of age with that among patients who were older than ?20 years of age (61 versus 68 respectively), the latter being higher with an OR 4.2 (p<0.0001). Conclusion: RMSF in hospitalized patients has a high mortality rate in spite of early treatment in all age groups, without showing any predominance in gender. However, patients older than 20 years of age had a higher mortality rate than those younger than 20 years, without any predominance in gender.